Hadith as a Lamp of Education: The Position and Relevance of Hadith in Contemporary Islamic Education - Afifah Salsa Bella; Romlah Abubakar Askar; Munzir Suparta (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
Hadith as the second source of Islamic teachings after the Koran has an important role in building the morals and character of the Muslim generation. Hadith is defined as all the sayings of the Prophet Muhammad SAW which can be used as evidence in establishing Sharia law, such as obligatory, haram, mandub, makruh and permissible. Hadith also includes all matters relating to the mission and teachings of Allah SWT carried out by the Prophet Muhammad SAW, while matters of a humanitarian nature are not included in the hadith category. This research uses a descriptive method with qualitative analysis and uses a library research approach that collects data through research, reading, and analysis of related documents. The research results show that with a deep understanding of hadith, it is hoped that educators and the community can integrate Islamic values ​​in the education process, so that future generations will not only have broad knowledge but also good morals. Thus, the importance of understanding and applying hadith in contemporary Islamic education cannot be ignored because this will contribute to the formation of a generation of Muslims who are not only intellectually intelligent but also strong in morals and spirituality.